Incidence of Clostridioides difficile infection at a Saudi Tertiary Academic Medical Center and compliance with IDSA/SHEA, ACG, and ESCMID guidelines for treatment over a 10-year period - Nouf A. Aljafel; Hadeel H. Al-Shaikhy; Maram A. Alnahdi; Abrar K. Thabit (Elsevier, 2020)
Background: Limited data currently exist on the incidence of Clostridioides difficile infection (CDI) in Saudi Arabia. Compliance with CDI treatment guidelines is prudent for proper management of the infection and preventing recurrence. Methods: This was an epidemiologic and retrospective cohort study to find the 10-year cumulative incidence of CDI (December 2007-January 2018) among patients presented with diarrhea or experienced diarrhea during hospitalization and the correlation between clinical outcomes and the compliance of treatment regimens with pertinent global guidelines (IDSA/SHEA, ACG, and ESCMID guidelines). Results: At our institution, the 10-year CDI cumulative incidence was 8.4%. A total of 170 patients were included in the analysis of compliance with the guidelines and clinical outcomes. Most patients had non-severe CDI according to all three guidelines. Clinical cure was found in 76.5% of the cases although all-cause mortality rate was 28.2%. Median (IQR) hospitalization period was 11 (5-29) days. Compliance with all three guidelines was significantly associated with clinical cure (R = 0.24-0.27; P ≤ 0.002). Lower mortality also significantly correlated with compliance with IDSA and ACG guidelines (P ≤ 0.03), but not with ESCMID guidelines (P = 0.05). While compliance with all three guidelines was associated with lower risk of recurrence, this finding was not statistically significant. Conclusion: CDI rates reported in this study were very low reflecting a low incidence at our institution. As guidelines were prepared by a panel of experts using most reliable evidence, results shown in this study indicate the importance of following guidelines recommendations for better patient outcomes.